Scrub Typhus and Influenza A Co-Infection: A Case Report - Chie Yamamoto; Ayano Maruyama; Jun Munakata; Tasuku Matsuyama; Keitaro Furukawa; Ryosuke Hamashima; Motohiko Ogawa; Yuki Hashimoto; Akiko Fukuda; Tohru Inaba; Yoko Nukui (Pathogens)
Scrub typhus, caused by Orientia tsutsugamushi, is a neglected and reemerging disease that causes considerable morbidity and mortality. It now extends beyond the Tsutsugamushi Triangle, the region wherein it has traditionally been endemic. Influenza has also resurged since the infection control measures against COVID-19 were relaxed. A few cases of scrub typhus and influenza co-infection have been reported. Herein, we report the case of a 74-year-old woman with fever and upper respiratory symptoms diagnosed with influenza A and treated with oseltamivir; however, her fever persisted, and she developed respiratory failure, liver dysfunction, headache, diarrhea, and an erythematous skin rash. She lived in a forested area where scrub typhus was endemic and worked on a farm. Physical examination revealed an eschar on her posterior neck, and she was diagnosed with scrub typhus and influenza A co-infection. After minocycline treatment, her symptoms improved within a few days. This is the first reported case of scrub typhus and influenza A co-infection in Japan. This case illustrates that co-infection should be suspected in patients with fever persisting after their initial infection has been treated and that in patients living in endemic areas, scrub typhus can occur concurrently with influenza. The symptoms of scrub typhus are flu-like and nonspecific, which may delay diagnosis and treatment.